An example of two non-unitarily equivalent compact operators with the same traces and kernel - Alcántara Bode, Julio (Pro Mathematica, 2009)
We give examples of two non nuclear non normal Hilbert-Schmidt operators that are not unitarily equivalent but have the same traces and kernel.